Teacher and Parent Communication Patterns in Increasing Student Learning Motivation in Elementary Schools - Yuliyanto, Aan; Ni’am, Rikhatun; Hidayati, Novi; Sofiasyari, Irma (EduBase : Journal of Basic Education, 2024)
Purpose: This research aims to describe the process, obstacles and solutions to teacher-parent communication patterns in increasing student learning motivation during the pandemic in grade 3 elementary school. Methods: This type of research is field research using Grounded Theory. Participants in this research were 20 parents and students as well as two teachers at an elementary school in Jepara. Data collection was carried out by interviews, observation and documentation with primary data sources including homeroom teachers, parents and students. The validity of the data uses a credibility test with triangulation techniques. Researchers carry out data analysis using several stages, namely problem formulation, use of theoretical studies (if necessary), data collection and sampling, data analysis, and drawing conclusions. Results: The results of the research show that: 1) Teacher and parent communication patterns in increasing student learning motivation during the pandemic in grade 3 elementary school are divided into three forms, namely: One-stage communication pattern, the communication pattern carried out by parents does not provide feedback to Teacher. Two-stage communication pattern: communication between teachers and parents has feedback. In the three-stage communication pattern, the communication carried out has feedback, and the communicant here can convey the information he obtains to other people. 2) Barriers to communication patterns, namely parents as communicants do not immediately provide feedback, and sometimes the feedback does not match the message conveyed by the teacher. 3) The solution is that parents must take the initiative in giving messages. Motivate children to be patient, open and empathetic, provide religious education as early as possible, and provide encouragement. Conclusion: This research reveals communication patterns between teachers and parents to increase student learning motivation during the pandemic. Communication patterns are divided into three stages, with challenges such as delayed feedback from parents. Thus, it is necessary to involve parents proactively, to take communication initiatives, form patience and empathy in children, provide religious education as early as possible, and provide ongoing support, thereby creating an environment that supports student motivation and learning.